2021
DOI: 10.1002/cjoc.202100115
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced NaI‐Promoted Radical Borylation of Alkyl Halides and Pseudohalides

Abstract: Main observation and conclusion A method for photoinduced NaI‐promoted radical borylation of aliphatic halides and pseudohalides with bis(catecholato)diboron (B2cat2) as the boron source is introduced. The borylation reaction is operationally simple and shows high functional group tolerance and broad substrate scope. Preliminary mechanistic studies suggest that the reaction proceeds through SN2‐based radical‐generation strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 39 publications
0
4
0
2
Order By: Relevance
“…The radical cascade cyclization of 2-(2-isocyanophenyl)­acetonitriles can break through the restrictions mentioned above by introducing aryl and alkyl groups along with the construction of quinoline skeletons and amine motifs, aryl radicals, and alkyl that can be generated from the corresponding aryl- or alkylborons upon suitable oxidations . As part of our ongoing interests in organoboron chemistry and being inspired by our previous works on isocyanides ,, and the works of Studer, Nagib, Chatani, and Lei, we envisioned that with 2-(2-isocyanophenyl)­acetonitrile as a radical acceptor and organoboron as a radical donor, an intermolecular radical addition to isocyanide would lead to an imidoyl radical, which could subsequently intramolecularly attack the cyanide group in 2-(2-isocyanophenyl)­acetonitrile to render the desired quinolin-3-amines. There are several challenges in our conjecture: (1) An appropriate condition should be found to promote the radical from organoboron compounds, which could not interrupt the following cyclization.…”
mentioning
confidence: 99%
“…The radical cascade cyclization of 2-(2-isocyanophenyl)­acetonitriles can break through the restrictions mentioned above by introducing aryl and alkyl groups along with the construction of quinoline skeletons and amine motifs, aryl radicals, and alkyl that can be generated from the corresponding aryl- or alkylborons upon suitable oxidations . As part of our ongoing interests in organoboron chemistry and being inspired by our previous works on isocyanides ,, and the works of Studer, Nagib, Chatani, and Lei, we envisioned that with 2-(2-isocyanophenyl)­acetonitrile as a radical acceptor and organoboron as a radical donor, an intermolecular radical addition to isocyanide would lead to an imidoyl radical, which could subsequently intramolecularly attack the cyanide group in 2-(2-isocyanophenyl)­acetonitrile to render the desired quinolin-3-amines. There are several challenges in our conjecture: (1) An appropriate condition should be found to promote the radical from organoboron compounds, which could not interrupt the following cyclization.…”
mentioning
confidence: 99%
“…Electrochemistry has become an important tool in organic synthesis. In 2021, Lu and co‐workers [78] reported an electrochemical borylation of alkyl halides (X=I, Br, Cl) (Scheme 49). Mechanistic studies revealed that B 2 cat 2 serves not only as the boron source, which also be reduced at the cathode and mediated the reduction of alkyl halides.…”
Section: Borylation Of C−x Bondsmentioning
confidence: 99%
“…因此, 开发更加 绿色、温和的脱羧偶联新方法具有重要意义.近年来, 可见光促进的有机合成有效避免了传统有 机反应的苛刻条件, 已经成为当前的研究前沿和热点领 域 [3][4][5][6][7][8][9][10][11][12][13] . 通过可见光促进反应的策略, 人们开发了许多 新型高效的有机合成方法 [14][15][16][17][18][19][20][21][22][23][24][25] . 特别值得注意的是, 雷 爱文等 [26] 由于贵金属光催化剂的价格昂贵, 且产物在纯化的 过程中容易产生金属残留等问题, 近年来, 人们发展了 多种无金属的有机光催化剂用于可见光诱导 α-酮酸类 化合物的化学转化.…”
unclassified
“…近年来, 可见光促进的有机合成有效避免了传统有 机反应的苛刻条件, 已经成为当前的研究前沿和热点领 域 [3][4][5][6][7][8][9][10][11][12][13] . 通过可见光促进反应的策略, 人们开发了许多 新型高效的有机合成方法 [14][15][16][17][18][19][20][21][22][23][24][25] . 特别值得注意的是, 雷 爱文等 [26]…”
unclassified